1980
DOI: 10.1111/j.1365-2648.1980.tb03350.x
|View full text |Cite
|
Sign up to set email alerts
|

Preserving the essence of nursing in a technological age*

Abstract: The author examines what the essence of nursing is. Then she goes on to seek the kind of administrators that will help preserve this essence. And the kind of research that will facilitate it as well as the practice manifested by it. She concludes that the essence of nursing —‐basic nursing care is essential to human welfare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 7 publications
0
46
0
Order By: Relevance
“…Kitson (1999) cited in Spilsbury and Meyer (2001) has identified two types of nursing intervention; (1) maintenance interventions which translates into doing the patient no harm and (2) therapeutic interventions, which translates into knowing how to do the patient some good. Earlier, Henderson (1980) suggested that nurses are ''rehabilitators par excellence''. Orthopaedic nursing includes rehabilitation, but Waters (1996) notes that the current nursing role in rehabilitation is very much secondary, largely being confined to ''general maintenance and carry-on'' functions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kitson (1999) cited in Spilsbury and Meyer (2001) has identified two types of nursing intervention; (1) maintenance interventions which translates into doing the patient no harm and (2) therapeutic interventions, which translates into knowing how to do the patient some good. Earlier, Henderson (1980) suggested that nurses are ''rehabilitators par excellence''. Orthopaedic nursing includes rehabilitation, but Waters (1996) notes that the current nursing role in rehabilitation is very much secondary, largely being confined to ''general maintenance and carry-on'' functions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, patients must collaborate significantly in their own care process, so that they support their own rehabilitation and become more able to exercise their decision-making power and regain their independence [15] . This active collaboration by patients is key to their social participation, which ensures their [22] ysical and auses and DCP model on depends limitations on's social h the DCP em in the is way, the 1,12] . Thus, f the nurse habilitation nurses so they can set appropriate intervention objectives for the patient's life experience and projects.…”
Section: Rehabilitation Care and The Role Of Nursesmentioning
confidence: 99%
“…The emancipation of the role, the specialization of the practice and nurses' recognition of their own role are some examples of these changes. It was Virginia Henderson [1] who suggested that nurses are, or at least have the potential to be, "rehabilitators par excellence". But what does that role involve?…”
Section: Introductionmentioning
confidence: 99%
“…The uniqueness of nurses as a professional group is temporally defined, since they are the only professionals who are in contact with patients 24 hours a day (Henderson, 1980). A major question that has underpinned numerous workload studies in nursing has been how much time nurses need to 'spend' with patients or more commonly how much time is needed for the completion of certain activities or tasks.…”
Section: Durational Expectanciesmentioning
confidence: 99%